Cordyceps guangdongensis lipid-lowering formula alleviates fat and lipid accumulation by modulating gut microbiota and short-chain fatty acids in high-fat diet mice - Wang, Gangzheng; Sun, Chengyuan; Xie, Bojun; Wang, Tao; Liu, Hongwei; Chen, Xianglian; Huang, Qiuju; Zhang, Chenghua; Li, Taihui; Deng, Wangqiu (Frontiers in Nutrition, 2022)
Obesity has caused serious health and economic problems in the world. Cordyceps guangdongensis is a high-value macrofungus with broad application potential in the food and bio-medicine industry. This current study aimed to estimate the role of C. guangdongensis lipid-lowering compound formula (CGLC) in regulating fat and lipid accumulation, gut microbiota balance, short-chain fatty acid (SCFA) contents, and expression levels of genes involved in fat and lipid metabolism in high-fat diet (HFD) mice. The results showed that CGLC intervention markedly reduced body weights and fat accumulation in HFD mice, improved glucose tolerance and blood lipid levels, and decreased lipid droplet accumulation and fat vacuole levels in the liver. CGLC decreased the ratio of Firmicutes and Bacteroidetes and increased the relative abundances of Bacteroides (B. acidifaciens) and Bifidobacterium (B. pseudolongum). In addition, CGLC treatment significantly promoted the production of SCFAs and regulated the relative expression levels of genes involved in fat and lipid metabolism in liver. Association analysis showed that several species of Bacteroides and most of SCFAs were significantly associated with serum lipid indicators. These results suggested that CGLC is a novel candidate formulation for treating obesity and non-alcohol fatty liver by regulating gut microbiota, SCFAs, and genes involved in fat and lipid metabolism.